Cobalt-free lithium-rich manganese-based positive electrode material and preparation method thereof

Cobalt-free lithium-rich manganese-based cathode material was prepared by co-precipitation method. The spherical particle structure wrapped with rod-like lines and the two calcining process under an oxygen atmosphere were used to solve the problems of scarcity of cobalt resources and insufficient performance of traditional cathode materials, and achieve efficient and environmentally friendly battery material production.

CN119890290APending Publication Date: 2025-04-25SICHUAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411882990.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Traditional lithium-ion battery cathode materials have problems such as scarcity of cobalt resources, environmental pollution and insufficient performance, especially lithium-rich manganese-based cathode materials have poor performance in the first circle of Coulombs, poor rate performance and severe voltage attenuation.

Method used

The co-precipitation method is used to prepare cobalt-free lithium-manganese-based positive electrode material. Through the spherical particle structure wrapped with rod-like lines, the specific surface area and active sites of the material are improved, and the use of cobalt elements is reduced. Two calcining processes under an oxygen atmosphere are used to form a material with the chemical formula of Li1.2Mn0.6Ni0.2O2.

Benefits of technology

It significantly reduces the cost of raw materials, improves the specific capacity and cycle stability of the cathode material, improves the electrochemical performance, is suitable for large-scale production, and is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of energy storage, and provides a cobalt-free lithium-rich manganese-based positive electrode material and a preparation method thereof.The cobalt-free lithium-rich manganese-based positive electrode material is a Li1. 2Mn0. 6Ni0. 2O2 positive electrode material, is of a spherical coil structure wound by rod-shaped lines, is large in specific surface area and good in fatigue resistance and can make full contact with electrolyte. A lithium ion battery prepared from the cobalt-free lithium-rich manganese-based positive electrode material is high in specific capacity, good in rate capability and stable in long circulation; and the method is simple in process, high in operability, easy to implement, low in cost, easy to industrialize and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery positive electrode material preparation, and in particular to a cobalt-free lithium-rich manganese-based positive electrode material and a preparation method thereof. Background Art

[0002] Since the first industrial revolution, fossil fuels have been the main component of the energy system and have driven the development of the economy and society. However, the greenhouse gases they produce have caused serious environmental pollution and climate change. Moreover, due to their non-renewable nature, these energy resources will eventually be exhausted. Therefore, for the sustainable development of resources and the environment, the global energy structure has shifted to low-carbon clean energy. Among clean energy sources such as solar energy, wind energy, water conservancy, and biomass energy, battery energy storage has attracted widespread attention due to its advantages of recyclability, portability, and high energy density.

[0003] Secondary batteries are the most commonly used energy storage batteries. Compared with nickel-cadmium batteries, lead-acid batteries, etc., lithium-ion batteries have the highest energy density in practical application batteries. In addition, lithium-ion batteries have the advantages of high operating voltage, low self-discharge and long cycle life, making them widely used in 3C electronic products such as mobile phones and laptops. They are also the main power source for new energy electric vehicles (EVs) and have good application prospects in the field of energy storage. As an energy storage element, the most important parameter index of lithium-ion batteries is electrochemical performance. As the main active material, the energy density of the positive electrode material is the main factor limiting the energy density and other indicators of lithium-ion batteries, and its cost accounts for about 40% of the total lithium-ion battery. Therefore, the development of low-cost and high-performance positive electrode materials is the key to the further development and application of lithium-ion batteries in the future.

[0004] Although traditional lithium-ion battery cathode materials such as lithium cobalt oxide materials and ternary layered oxide materials have achieved remarkable success in commercial applications, the scarcity of resources such as cobalt and nickel and the environmental problems in their mining process make it more important to develop new cobalt-free / low-cobalt cathode materials. Compared with traditional commercial cathodes such as lithium cobalt oxide (175 mAh g-1) and lithium iron phosphate (140 mAh g-1), lithium-rich manganese-based cathode materials can provide a high capacity of more than 250 mAh g-1 due to the joint participation of anions and cations in the redox reaction, making them one of the most promising cathode materials for high energy density batteries. However, lithium-rich manganese-based cathode materials still face many challenges, such as low coulombic efficiency in the first cycle, poor rate performance and severe voltage decay.

[0005] The preparation method is an important factor affecting the positive electrode material of lithium-ion batteries. The most commonly used methods for lithium-rich positive electrode materials are solid phase reaction method, sol-gel method, co-precipitation method, etc. Among them, it is difficult to achieve a level of uniform mixing for the materials prepared by the solid phase reaction method; the solution gel method requires a large amount of expensive organic acid or alcohol to be consumed during the preparation process, which is costly and not suitable for large-scale production. The co-precipitation method is a method of obtaining a precursor with uniform element distribution through the complexation of ammonium ions, the synergistic effect of environmental pH, temperature, feed rate and other conditions, and then mixing it with lithium salts, and combining it with a high-temperature calcination process to obtain a lithium-rich manganese-based positive electrode material. This method can make the various elements evenly distributed, the process is simple, the raw materials are cheap, and it can meet the needs of continuous large-scale production.

[0006] The idea of ​​the present invention is to prepare a spherical particle structure formed by winding rod-like wires. This special structure has a large specific surface area, which is conducive to full contact between the electrolyte and the positive electrode material and improves the Li + The ion migration rate is increased, more active sites are added, and the volume and internal stress changes during the cycle are alleviated, thereby improving the specific capacity and cycle stability of lithium-rich manganese-based positive electrode materials. At present, there is no preparation of lithium-rich manganese-based positive electrode materials with a spherical particle structure wrapped with rod-like lines. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a cobalt-free lithium-rich manganese-based positive electrode material and a preparation method thereof, so as to improve the performance of the lithium-rich manganese-based positive electrode material.

[0008] To achieve the above object, the technical solution of the present invention is as follows:

[0009] In the first aspect, the present invention provides a cobalt-free lithium-rich manganese-based positive electrode material, the chemical formula of the cobalt-free lithium-rich manganese-based positive electrode material is: Li 1.2 Mn 0.6 Ni 0.2 O2.

[0010] Since cobalt is expensive and scarce, the lithium-rich manganese-based positive electrode material provided by the present invention does not contain cobalt, thereby significantly reducing the cost of raw materials and is not limited by mineral resources. By preparing a cobalt-free lithium-rich manganese-based positive electrode material with a large specific surface area, it is beneficial for the electrolyte to fully contact the positive electrode material and improve the Li + The ion migration rate, the increase of more active sites and the alleviation of volume and internal stress changes during the cycle process significantly improve the electrochemical performance of the positive electrode material, which is conducive to large-scale promotion and application.

[0011] In a second aspect, the present invention provides a method for preparing the cobalt-free lithium-rich manganese-based positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0012] Step 1: dissolving nickel salt and manganese salt in deionized water according to a molar ratio to obtain a mixed metal salt solution;

[0013] Step 2: adding the metal salt solution, the precipitant solution and the complexing agent solution into the base solution respectively by using a peristaltic pump to carry out a co-precipitation reaction to obtain a cobalt-free lithium-rich manganese-based precursor;

[0014] Step 3: Mix the cobalt-free lithium-rich manganese-based precursor and the lithium salt according to a stoichiometric ratio and calcine twice in an oxygen atmosphere to obtain a cobalt-free lithium-rich manganese-based positive electrode material.

[0015] The present invention adopts a coprecipitation method to prepare a lithium-rich manganese-based precursor, and then obtains a cobalt-free lithium-rich manganese-based positive electrode material through two subsequent calcinations, and the calcinations are performed under an oxygen atmosphere, thereby preparing a structure with a larger specific surface area and improving the capacitance of the positive electrode material.

[0016] Preferably, the nickel salt and manganese salt in step 1 are any one of sulfate, nitrate, acetate or chloride salts of the corresponding metal ions.

[0017] Preferably, the molar ratio of nickel ions to manganese ions in the metal salt solution in step 1 is (0.10-0.30):(0.20-0.70), for example, it can be 0.15:0.40, 0.20:0.60 or 0.30:0.65, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] Preferably, the total concentration of metal ions in the metal salt solution in step 1 is 1.5-3.0 mol / L, for example, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L or 3.0 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, the precipitant solution in step 2 comprises sodium hydroxide solution and / or sodium carbonate solution.

[0020] Preferably, the complexing agent solution in step 2 includes any one of ammonia water, sodium citrate solution or ethylenediaminetetraacetic acid solution.

[0021] Preferably, the base solution in step 2 is a mixed solution of sodium sulfate solution and a complexing agent, and the concentration of the sodium sulfate solution is 1.5-3.0 mol / L;

[0022] Preferably, the pH value of the coprecipitation reaction in step 2 is 8.0-12.0, for example, it can be 9.0, 9.5, 10.0, 11.0, or 12.0, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] Preferably, the temperature of the coprecipitation reaction in step 2 is 45-65°C, for example, 45°C, 50°C, 55°C, 60°C or 65°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Preferably, the coprecipitation reaction in step 2 is carried out in a protective gas atmosphere, and the protective gas atmosphere includes any one of nitrogen, helium or argon.

[0025] Preferably, the coprecipitation reaction in step 2 is accompanied by stirring, and the stirring rate is 600-1000 r / min, for example, it can be 600 r / min, 700 r / min, 800 r / min, 900 r / min or 1000 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Preferably, the lithium salt in step three includes lithium hydroxide and / or lithium carbonate.

[0027] Preferably, the lithium carbonate or lithium hydroxide used in the preparation process in step 3 is in excess of 5%.

[0028] Preferably, the calcination temperature in step three, the first calcination temperature is 450-500°C, for example, it can be 450°C, 475°C or 500°C, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] Preferably, the calcination temperature in step three, the second calcination temperature is 800-950°C, for example, it can be 800°C, 850°C, 900°C or 950°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the second calcination time in step three is 12-16 hours, for example, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the cobalt-free lithium-rich manganese-based positive electrode material as described in the first aspect.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The lithium-rich manganese-based positive electrode material provided by the present invention does not contain cobalt elements, thereby significantly reducing the cost of raw materials and is not limited by mineral resources. The preparation and synthesis process is simple, the production efficiency is high and it is suitable for large-scale production. In addition, it also has the advantages of huge yield of the obtained product, good control of reaction conditions, and good repeatability of results. The cobalt-free system in the present invention is cheaper and more environmentally friendly than the cobalt-containing system, and the lithium-rich positive electrode material prepared by the present invention has a large specific surface area, which is conducive to full contact between the electrolyte and the positive electrode material and improves Li + The ion migration rate is increased, more active sites are added, and the changes in volume and internal stress during the cycle are alleviated, thereby improving the specific capacity and cycle stability of lithium-rich manganese-based positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 This is a scanning electron microscope (SEM) image of the final product prepared in Example 1.

[0036] Figure 2 This is the EDS spectrum of the final product prepared in Example 1.

[0037] Figure 3 XRD diffraction patterns of the cobalt-free lithium-rich manganese-based positive electrode materials prepared in Example 1, Example 2 and Example 3.

[0038] Figure 4 The first cycle charge and discharge curves of the cobalt-free lithium-rich manganese-based positive electrode materials prepared in Example 1, Example 2 and Example 3.

[0039] Figure 5 This is a comparison chart of the rate performance of the cobalt-free lithium-rich manganese-based positive electrode materials of Example 1 and Example 2. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0041] In the following examples and comparative examples, the material characterization and analysis instruments and methods used are as follows:

[0042] Scanning electron microscope (SEM) test & EDS spectrum test: Use scanning electron microscope (JSM-7500F, JEOL) to observe the surface microstructure and element distribution of materials;

[0043] X-ray diffraction (XRD) test: X-ray diffractometer, model X'Pert Pro MPD DY129, PANalytical, was used to analyze the phase structure of the material;

[0044] Electrochemical cycle test: Use a charge and discharge tester, the instrument model is BTS-3000, Xinwei Electronics, to test the electrochemical properties of the material;

[0045] Assembly and testing of CR2025 button cells: The positive electrode material (the final product prepared in the example), acetylene black, and polyvinylidene fluoride (PVDF) were made into a slurry in a mass ratio of 8:1:1 and coated on an aluminum foil. The dried aluminum foil loaded with the slurry was cut into small discs with a diameter of 1.4 cm using a cutting machine as the positive electrode. A metal lithium sheet was used as the negative electrode, Celgard2500 was used as the diaphragm, and a 5V high-voltage carbonate electrolyte was used to assemble the CR2025 button cell in an argon atmosphere glove box.

[0046] Embodiment 1:

[0047] This embodiment provides a cobalt-free lithium-rich manganese-based positive electrode material and a preparation method thereof, the chemical formula of which is: Li 1.2 Mn 0.6 Ni 0.2 O2 is prepared by the following steps:

[0048] Dissolve NiSO4·6H2O and MnSO4·H2O in deionized water to obtain 2 mol L -1 50 ml of transition metal salt solution. NaOH was dissolved in deionized water to obtain 4 mol L -1 Prepare 50 ml of 2 mol L - 1 Na2SO4 solution was injected into the round-bottom flask and then heated to 55°C in a water bath for later use. The above two solutions were pumped at a rate of 5 mL min -1 The rate was pumped into the three-necked flask at the same time, and a concentration of 0.5 mol L -1 The whole process was carried out in a N2 environment with a stirring speed of 800 r / min and a pH value of 12. After the feeding was completed, the mixture was stirred for 8 hours and aged for 5 hours, then filtered and washed and dried at 60°C for 12 hours to obtain the precursor Mn 0.75 Ni 0.25Subsequently, the precursor was ground with an excess of 5% LiOH·H2O in a mortar and sintered at 500°C and 900°C for 5h and 12h in an O2 atmosphere to obtain a cobalt-free lithium-rich manganese-based cathode material. Figure 1 This is a scanning electron microscope photograph of the cobalt-free lithium-rich manganese-based positive electrode material prepared in Example 1. From the figure, it can be seen that the sample has a relatively uniform particle size and good density. It is a spherical particle structure formed by winding rod-like lines and has a large specific surface area. Figure 3 The XRD diffraction pattern of the cobalt-free lithium-rich manganese-based positive electrode material prepared in Example 1 is compared with the standard card (PDF#85-1969), which shows that the main strong characteristic peaks belong to the hexagonal α-NaFeO2 (space group R-3m) structure, and the weak superlattice peak of 20°-22° comes from the Li2MnO3 phase of the C / 2m space group.

[0049] Embodiment 2:

[0050] This embodiment provides a cobalt-free lithium-rich manganese-based positive electrode material and a preparation method thereof, the chemical formula of which is: Li 1.2 Mn 0.6 Ni 0.2 O2 is prepared by the following steps:

[0051] Dissolve NiSO4·6H2O and MnSO4·H2O in deionized water to obtain 2 mol L -1 50 ml of transition metal salt solution. NaOH was dissolved in deionized water to obtain 4 mol L -1 Prepare 50 ml of 2 mol L - 1 Na2SO4 solution was injected into the round-bottom flask and then heated to 55°C in a water bath for later use. The above two solutions were pumped at a rate of 5 mL min -1 The rate was pumped into the three-necked flask at the same time, and a concentration of 0.5 mol L -1 The whole process was carried out in a N2 environment with a stirring speed of 800 r / min and a pH value of 11. After the feeding was completed, the mixture was stirred for 8 hours and aged for 5 hours, then filtered and washed and dried at 60°C for 12 hours to obtain the precursor Mn 0.75 Ni 0.25 Subsequently, the precursor was ground with an excess of 5% LiOH·H2O in a mortar and sintered at 500°C and 900°C for 5h and 12h in an O2 atmosphere to obtain a cobalt-free lithium-rich manganese-based cathode material.

[0052] Embodiment 3:

[0053] This embodiment provides a cobalt-free lithium-rich manganese-based positive electrode material and a preparation method thereof, the chemical formula of which is: Li 1.2 Mn 0.6 Ni 0.2 O2 is prepared by the following steps:

[0054] Dissolve NiSO4·6H2O and MnSO4·H2O in deionized water to obtain 2 mol L -1 50 ml of transition metal salt solution. NaOH was dissolved in deionized water to obtain 4 mol L -1 Prepare 50 ml of 2 mol L - 1 Na2SO4 solution was injected into the round-bottom flask and then heated to 55°C in a water bath for later use. The above two solutions were pumped at a rate of 5 mL min -1 The rate was pumped into the three-necked flask at the same time, and a concentration of 0.5 mol L -1 The whole process was carried out in a N2 environment with a stirring speed of 800 r / min and a pH value of 12. After the feeding was completed, the mixture was stirred for 8 hours and aged for 5 hours, then filtered and washed and dried at 60°C for 12 hours to obtain the precursor Mn 0.75 Ni 0.25 Subsequently, the precursor was ground with an excess of 5% LiOH·H2O in a mortar, and sintered at 500°C and 900°C for 5h and 12h in an air atmosphere to obtain a cobalt-free lithium-rich manganese-based cathode material.

Claims

1. A cobalt-free lithium-rich manganese-based positive electrode material and a preparation method thereof, characterized in that: The chemical formula of the cobalt-free lithium-rich manganese-based positive electrode material is Li 1.2 Mn 0.6 Ni 0.2 O2, the positive electrode material has a good layered structure, the particle size is small, only 20-30μm, and the distribution is uniform. The particles are rod-shaped spherical particles and are evenly distributed without obvious agglomeration.

2. A method for preparing a cobalt-free lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The following steps are involved: Step 1: dissolving nickel salt and manganese salt in deionized water according to the molar ratio to obtain a mixed metal salt solution; Step 2: adding the metal salt solution, precipitant solution and complexing agent solution obtained in step 1 into the base liquid respectively by using a peristaltic pump to carry out a co-precipitation reaction, and then aging, centrifuging, washing and drying to obtain a cobalt-free lithium-rich manganese-based precursor; Step 3: The cobalt-free lithium-rich manganese-based precursor and lithium salt in step 2 are mixed according to a stoichiometric ratio and calcined in an oxygen atmosphere to obtain a cobalt-free lithium-rich manganese-based positive electrode material.

3. The preparation method according to claim 2, characterized in that: In the step 1, the nickel salt and the manganese salt are any combination of sulfate, acetate, nitrate or chloride of the corresponding metal ions; Preferably, the total concentration of metal ions in the metal salt solution in step 1 is 1.5-3.0 mol / L.

4. The preparation method according to claim 2, characterized in that: In the step 2, the precipitant solution includes a sodium hydroxide solution or a sodium carbonate solution, and the molar ratio is calculated, that is, the molar amount of sodium hydroxide: the total molar amount of Mn and Ni is 2:1, and the molar amount of sodium carbonate: the total molar amount of Mn and Ni is 1:1; Preferably, the complexing agent solution in step 2 comprises one of ammonia water, ethylenediaminetetraacetic acid or sodium citrate solution; Preferably, the base solution in step 2 is a mixed solution of sodium sulfate solution and a complexing agent, and the concentration of the sodium sulfate solution is 1.5-3.0 mol / L; Preferably, the pH value of the coprecipitation reaction in step 2 is 8.0-12.

0.

5. The preparation method according to any one of claims 2 to 4, characterized in that: In the step 2, the temperature of the coprecipitation reaction is 45-65°C; Preferably, the coprecipitation reaction in step 2 is carried out in an inert gas atmosphere, and the inert gas atmosphere includes any one of argon, nitrogen or helium; Preferably, the coprecipitation reaction in step 2 is accompanied by stirring, and the stirring rate is 600-1000 r / min.

6. The preparation method according to any one of claims 2 to 5, characterized in that: In the step 3, the lithium salt includes lithium hydroxide and / or lithium carbonate; Preferably, the lithium carbonate or lithium hydroxide used in the preparation process in step 3 is in excess of 5%.

7. The method for preparing a cobalt-free lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The calcination in step three is to first increase the temperature to 450-500°C at a rate of 3-5°C / min for pre-calcination for 5 hours, and then increase the temperature to 800-950°C at a rate of 3-5°C / min for pre-calcination for 12 hours to 16 hours.

Citation Information

Patent Citations

  • Lithium-rich manganese-based material and preparation and application thereof

    CN109904402A

  • Cobalt-free high-nickel ternary positive electrode material, preparation method thereof and method for preparing battery positive electrode

    CN113809294A

  • Battery positive electrode material and preparation method thereof

    CN116979043A

  • Synthesis and application of trace Bi modified cobalt-free lithium-rich manganese-based positive electrode material

    CN117023658A

  • Surface modification method and application of cobalt-free lithium-rich positive electrode material

    CN118738256A